Optimizing Adolescent Psychological Well-Being through an Environmental Ecological Approach - Murdianto Murdianto; Samsudin Samsudin; Ahmad Kirom; Nanik Setyowati; Suci Midsyahri Azizah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Psychological well-being is a general term used to describe an individual's mental health concerning the fulfillment of positive indicators of psychological functioning. Psychological well-being can be characterized as an indicator of good mental functioning and the drive to explore the potential of the individual as a whole to achieve success. This writing aims to explain the practice of counseling psychological well-being for adolescents using the benefits of environmental ecology introduced by Uri Bronfenbrenner, a psychologist from Cornell University, United States. Ecological theory views that the environmental context influences human development. The research method uses descriptive qualitative research methods. The researcher explains the activities, starting from preparation, implementation, and evaluation. The research results show that adolescent mental health assistance through an ecological approach goes very well. Great environmental ecology influences adolescents' psychological well-being.